2013
DOI: 10.1590/s1809-29502013000100013
|View full text |Cite
|
Sign up to set email alerts
|

Análise de parâmetros funcionais relacionados aos fatores de risco ocupacionais da atividade de enfermeiros de UTI

Abstract: | Evaluating factors such as fatigue and functional aspects can identify overloads during nursing activities. The aim was to evaluate need for recovery, prevalence of musculoskeletal discomfort, working capacity and perceived exertion of Intensive Care Unit (ICU) nurses. Twentyfour nurses participated (aged 40±8 years; 10 men and 14 women). The Nordic musculoskeletal questionnaire, work ability index (WAI), need for recovery scale (NRE) and scale of perceived exertion (Borg) were applied. Gender differences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
1
5
0
17
Order By: Relevance
“…A caracterização da amostra contendo os dados de estatura, peso e IMC foram avaliados e registrados (Tabela 1). (TEIXEIRA, 2011;NERY et al, 2013).…”
Section: Resultsunclassified
“…A caracterização da amostra contendo os dados de estatura, peso e IMC foram avaliados e registrados (Tabela 1). (TEIXEIRA, 2011;NERY et al, 2013).…”
Section: Resultsunclassified
“…20,23 The same was observed in two other studies carried out in Brazil, where one showed the prevalence of 75% of musculoskeletal discomfort in nurses who worked in intensive care units; therefore, another study concluded that 59.3% had musculoskeletal diseases and other comorbidities, such as cardiorespiratory and endocrine problems, being highlighted as factors predisposing to decreased work capacity, withdrawal and absenteeism. 14,27 It was revealed, in a study carried out in the city of Goiânia (GO), between the years of 2008 and 2012, through the analysis of 435 nursing dossiers, that, among the main reasons for leaving the work, those related to the system osteomuscular, with 19.70%, followed by mental and behavioral disorders, with 18.04%. It should be noted that this group of diseases is what most represents the reasons for leaving, attested and, in more serious cases, the definitive removal of the profession; 28,20 however, another study concluded that there is not always a significant relationship between the WAI and the existence of musculoskeletal comorbidities, even in the cases of those professionals who have some discomfort related to this comorbidity and who were classified as low capacity for work.…”
Section: Association Of Chronic Diseases and Ability To Workmentioning
confidence: 99%
“…Além disso, a fadiga altera o estado de alerta e vigília, assim como a motivação. 7,8 O trabalho docente é caracterizado por envolver modelos de produção e prestação de serviços que exigem uma adequação em um formato acelerado e intensificado, indicando um aumento da produtividade através do aumento do ritmo, da carga, da responsabilidade de trabalho, e da redução das pausas para descanso. 5 Observou-se que o exercício da docência sofre influência de diversas condições, sobretudo, as condições do ambiente, mobiliário, estrutura física, carga horária, tipo de atividade, relacionamento interpessoal, características relacionadas ao prazer em realizar a atividade laboral, sobrecarga de trabalho, entre outras.…”
Section: Aspectos éTicosunclassified
“…1,10 Estudos dos níveis de fadiga e capacidade para o trabalho proporcionam a obtenção de uma medida relevante em saúde através da identificação precoce da ocorrência de sobrecargas e a compreensão dos fatores envolvidos no desenvolvimento. 8 Diante do exposto, o objetivo desta pesquisa é verificar a influência da fadiga ocupacional na capacidade para o trabalho de professores do Centro de Ciências Biológicas de uma IES pública da cidade de Campina Grande/PB. Considerando as variáveis sociodemográficas, foi visto que as variáveis sexo (p<0,004) e ocorrência de problemas para dormir (p<0,000) demonstraram associação estatisticamente significativa (p<0,05) com o escore do QFY.…”
Section: Aspectos éTicosunclassified